Research Trends and Intellectual Structure of Business Impact Analysis: A Bibliometric Perspective - Judijanto, Loso; Sopyan, Sopyan (Eastasouth Institute, 2025)
This study aims to map the evolution and intellectual structure of Business Impact Analysis (BIA) using a bibliometric approach with VOSviewer. Data were collected from the Scopus database, covering publications related to BIA and its intersection with sustainability, digital transformation, innovation, and artificial intelligence. The bibliometric mapping reveals that research in this area has increasingly shifted from traditional themes such as risk management and financial performance toward broader concerns, including sustainable development, environmental impact, and corporate governance. Keyword co-occurrence analysis highlights “sustainable development,” “innovation,” and “digital transformation” as central clusters, reflecting the growing integration of BIA into global sustainability and technological agendas. This study contributes to theory by expanding the conceptual boundaries of BIA research and provides practical insights for policymakers, organizations, and practitioners in enhancing resilience and competitiveness. Limitations include reliance on a single database and exclusion of non-indexed literature, suggesting avenues for future research.